Elevated temperature adhesion of bioinspired polymeric micropatterns to glass. (December 2017) - Barreau, Viktoriia; Yu, Dan; Hensel, René; Arzt, Eduard
Abstract: Micropatterned polymer surfaces that operate at various temperatures are required for emerging technical applications such as handling of objects or space debris. As the mechanical properties of polymers can vary significantly with temperature, adhesion performance can exhibit large variability. In the present paper, we experimentally study temperature effects on the adhesion of micropatterned adhesives (pillar length 20 µm, aspect ratios 0.4 and 2) made from three different polymers, i.e., polydimethylsiloxane (PDMS), perfluoropolyether dimethacrylate (PFPEdma), and polyurethane (PU-ht). PU specimens showed the highest pull-off stresses of about 57 kPa at 60 °C, i.e., more than twice the value of unpatterned control samples. The work of separation similarly showed a maximum at that temperature, which was identified as the glass transition temperature, T g . PDMS and PFPEdma specimens were tested above their T g . As a result, the adhesion properties decreased monotonically (about 50% for both materials) for temperature elevation from 20 to 120 °C. Overall, the results obtained in our study indicate that the operating temperature related to the glass transition temperature should be considered as a significant parameter for assessing the adhesion performance of micropatterned adhesives and in the technical design of adhesion devices. Graphical abstract: